Mediating role of electronic word of mouth affecting green consumer behavior - Nga, Nguyen Thi Ngoc; Khoi, Bui Huy (International Journal of Management and Sustainability, 2024)
The research was conducted to measure the relationship between factors affecting green consumer behavior, examining the mediating role of E-WOM. To achieve the proposed research goals, the authors chose the Covariance-Based Structural Equation Modeling (CB-SEM) to analyze data when surveying 294 consumers living in Ho Chi Minh City with an interest in and understanding consumer products. Electronic word-of-mouth activities and green consumer behavior rely on a non-probability sampling method through structured interview questionnaires. The study employs the dual theory, which combines the information acceptance model (IAM) and the planned behavior model (TPB), as its background theory. Using Smart-PLS 4.0 statistical software to analyze data, statistical results have shown that the factors of Argument Quality (0.470), Reliable Source (0.175), and Satisfaction (0.388) have a positive impact on E–WOM (0.388). E-WOM has a positive and direct influence on green consumer behavior. The authors anticipate that their management implications will serve as a valuable solution for businesses embracing sustainable trends in the future.